Evaluating The Performance for DCF Protocol and EDCA Protocol (Jurnal Teknologi (Sciences & Engineering), 2015)
Nowadays supporting quality of service (QOS) for real time application is the main challenge of the wireless area network. 802.11standards use distributed Coordination Function (DCF) protocol and Enhanced Distributed Channel Access (EDCA) protocol in the MAC layer. DCF protocol has only one queue for different data types, it deals with data depending on the arriving time. There is no priority to serve real time applications faster. However EDCA protocol has four queues and each queue works with specific data type. Voice, video, best effort and background are the different queues in the EDCA protocol. Different parameters and priorities are defined for each queue. The voice queue reserves the highest priority and serves its data first. In this paper QOS parameters are measured for both DCF and EDCA protocol by using OPNET simulation. The QOS parameters must reach the requirements to support QOS. The results show how QOS parameters do not reach the requirements when using DCF protocol. The values of the end to end delay and the packet loss percentage are 0.514second, 19.04% respectively. But, when using EDCA protocol the end to end delay becomes 0.0624 second and the percentage of the packet loss decreases until reach 0.00617%. So the QOS parameters achieve requirements with EDCA protocol and support QOS.